2013
DOI: 10.1523/jneurosci.3101-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Transformation of Frequency Organization in Auditory Cortex

Abstract: The mammalian neocortex is a six-layered structure organized into radial columns. Within sensory cortical areas, information enters in the thalamorecipient layer and is further processed in supra- and infra-granular layers. Within the neocortex, topographic maps of stimulus features are present, but whether topographic patterns of active neurons change between laminae is unknown. Here, we used in vivo two-photon Ca2+ imaging to probe the organization of the mouse primary auditory cortex and show that the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
130
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(161 citation statements)
references
References 42 publications
27
130
4
Order By: Relevance
“…The third type of evidence for local order in A1 comes from recent in vivo 2-photon Ca 2+ imaging of layer 4 and layer 2/3 neurons in the same animal. This study demonstrated directly that the representation of frequency is much more homogeneous in layer 4 than in layer 2/3 [75] (Fig. 2b).…”
Section: High Resolution Imaging: Beyond Smooth Tonotopymentioning
confidence: 72%
See 1 more Smart Citation
“…The third type of evidence for local order in A1 comes from recent in vivo 2-photon Ca 2+ imaging of layer 4 and layer 2/3 neurons in the same animal. This study demonstrated directly that the representation of frequency is much more homogeneous in layer 4 than in layer 2/3 [75] (Fig. 2b).…”
Section: High Resolution Imaging: Beyond Smooth Tonotopymentioning
confidence: 72%
“…First, while responses of simultaneously imaged cells were heterogeneous, neurons did show high noise correlation suggesting that they might form interconnected networks [65, 73, 74]. These noise correlations decreased with distance between neurons, with a spatial scale of about 100 microns [65, 75] (see also [76]), suggesting that neuronal interactions are organized within anatomical columns. Second, different Ca 2+ dyes have different affinity for Ca 2+ and thus can report different aspects of the neural response.…”
Section: High Resolution Imaging: Beyond Smooth Tonotopymentioning
confidence: 99%
“…A previous study in awake marmosets found a high proportion of combination-selective, nontoneresponsive, and low spontaneous-firing neurons at superficial cortical depths in A1 (49). A two-photon imaging study showed that A1 neurons in layer IV respond more strongly to pure tones than neurons in upper layers (56). To fully understand the hierarchical auditory processing of harmonic information, it will be important to investigate the circuitry basis of HTNs and their connectivity to other neurons in auditory cortex in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…Perhaps, highly active and tonotopically organized neurons predominate in layer IV, while weakly responding and poorly tuned neurons prevail in superficial layers II/III of cortex. A recent two-photon study argues for such a scenario via explicit comparison of responses in layers IV and II/III (Winkowski and Kanold, 2013). However, the majority of neurons investigated in the present study are from layers II/III (Figure S1Q), which nonetheless exhibit strong tonotopicity (Figures 6A–C).…”
Section: Discussionmentioning
confidence: 99%